Potential Inhibition of Major Human Cytochrome P450 Isoenzymes by Selected Tropical Medicinal Herbs—Implication for Herb–Drug Interactions. (2019)
Background: Increasing use of medicinal herbs as nutritional supplements and traditional medicines for the treatment of diabetes, hypertension, hyperlipidemia, and malaria fever with conventional drugs poses possibilities of herb–drug interactions (HDIs). The potential of nine selected widely used tropical medicinal herbs in inhibiting human cytochrome P450 (CYP) isoenzymes was investigated. Materials and methods: In vitro inhibition of eight major CYP isoenzymes by aqueous extracts of Allium sativum, Gongronema latifolium, Moringa oleifera, Musa sapientum, Mangifera indica, Tetracarpidium conophorum, Alstonia boonei, Bauhinia monandra, and Picralima nitida was estimated in human liver microsomes by monitoring twelve probe metabolites of nine probe substrates with UPLC/MS-MS using validated N-in- One assay method. Results: Mangifera indica moderately inhibited CYP2C8, CYP2B6, CYP2D6, CYP1A2, and CYP2C9 with IC50 values of 37.93, 57.83, 67.39, 54.83, and 107.48 μg/ml, respectively, and Alstonia boonei inhibited CYP2D6 (IC50 = 77.19 μg/ml). Picralima nitida inhibited CYP3A4 (IC50 = 45.58 μg/ml) and CYP2C19 (IC50 = 73.06 μg/ml) moderately but strongly inhibited CYP2D6 (IC50 = 1.19 μg/ml). Other aqueous extracts of Gongronema latifolium, Bauhinia monandra, and Moringa oleifera showed weak inhibitory activities against CYP1A2. Musa sapientum, Allium sativum, and Tetracarpidium conophorum did not inhibit the CYP isoenzymes investigated. Conclusion: Potential for clinically important CYP-metabolism- Mediated HDIs is possible for Alstonia boonei, Mangifera indica, and Picralima nitida with drugs metabolized by CYP 2C8, 2B6, 2D6, 1A2, 2C9, 2C19, and 3A4. Inhibition of CYP2D6 by Picralima nitida is of particular concern and needs immediate in vivo investigations.